Invasor (in)conveniente: o manejo de javali como política pública - Guillardi, Bruno Luiz (2019)
This master thesis aims to demonstrate the implementation of wild boar management as a State Public Policy, especially in the state of São Paulo. Thus, we seek to explain the possible causes of the introduction and spread of wild boars (Sus scrofa) within the Brazilian territory, as well as the reasons that caused their demographic growth, a fact that has caused several economic, environmental and social damages throughout the country. Faced with this scenario, the Brazilian Institute of Environment and Renewable Natural Resources (IBAMA) eventually released the management, via slaughter, as a way to try to control its proliferation. However, given the lack of resources (human and financial) of the Brazilian State, it was up to individuals and companies to take over the management of wild boars, ie, while the State would be responsible for legislation and supervision, people who wanted, for some reason. For this reason, controlling wild boars could, with proper authorization, do so. Initially, in the state of São Paulo, the person responsible for releasing and overseeing management was the State Secretariat of the Environment (SMA) through its regionalized departments. Subsequently, this changed, with IBAMA being in charge of the registration and accountability of managers, while SMA along with the police agencies would be responsible for enforcement. However, the problem lies in the changes in management laws that are being changed too much - sometimes by the state government, sometimes by the federal government -, showing that the perspectives of action of those who build the management policy, the state organs, compared to those who carry out the control, the managers are not the same. Therefore, the problem of wild boar spread may persist or even worsen. Thus, in this paper, besides just trying to demonstrate the possible beginning of the introduction of wild boars in Brazil and the probable damages caused by their proliferation, we tried to contribute with some considerations and considerations, presenting different perspectives, often conflicting, of the State legislator/inspectors and control agents, in order to better clarify the management of wild boar as a Public Policy.